Life is different now – impacts of eating disorders on Carers in New Zealand: a qualitative study - Louise Fletcher; Henrietta Trip; Rachel Lawson; Nicki Wilson; Jennifer Jordan (Journal of Eating Disorders, 2021)
Plain English summary Eating disorders (EDs) are serious illnesses with a challenging treatment journey that often requires significant input from family members as carers. This study investigated perspectives and experiences of those caring for family members with an ED diagnosis. Carers reported significant impacts on many facets of their lives. The findings revealed levels of emotional and psychological stress both during and beyond the treatment journey. For carers ‘normal’ life was profoundly impacted by the complicated and often unanticipated role of treatment provider, and navigating the maze of treatment while trying to understand the diagnosis itself. For those with other children, the impacts were compounded by the distress also witnessed in those children. Relationships were significantly affected by the demands of treatment and the serious consequences of the disorder, as well as misunderstandings and stigma related to EDs. A ‘new normal’ state of constant worry and ongoing vigilance defined life post-diagnosis. The results indicate the impacts of an ED diagnosis in a loved one, and the demands of caring for that person and assuming the role of treatment provider were life-changing. For these carers, ‘life is different now’.